A thermally stable and reversible microporous hydrogen-bonded organic framework: aggregation induced emission and metal ion-sensing properties. Issue 45 (29th October 2015) - Zhou, Hui; Ye, Qun; Wu, Xiangyang; Song, Jing; Cho, Ching Mui; Zong, Yun; Tang, Ben Zhong; Hor, T. S. Andy; Yeow, Edwin Kok Lee; Xu, Jianwei
Abstract : A hydrogen-bonded organic framework derived from a polyhedral oligomeric silsesquioxane and an aggregation-induced emission luminogen tetraphenylethene derivative was reported. Abstract : A microporous hydrogen-bonded organic framework (HOF) derived from a polyhedral oligomeric silsesquioxane (POSS) intermediate and an aggregation-induced emission (AIE) luminogen tetraphenylethene (TPE) derivative has been synthesized and structurally characterized by various methods. This unique HOF exhibits a permanent porosity with a Brunauer–Emmett–Teller (BET) surface area of 101.9 m 2 g −1 . This HOF could be well dispersed in organic solvents in the form of nanoparticles with a size of a few hundred nanometers. These nanoparticles are highly fluorescent in organic solution, and exhibit a high fluorescence quenching selectivity towards copper ions. Furthermore, the fluorescence of this HOF could be recovered by the removal of copper ions upon addition of cyanide and, more interestingly, this process could be repeated several times without considerably sacrificing the sensing activity towards copper ions.